On-farm inoculants based on arbuscular mycorrhizal fungi on wheat performance - Fornari, Michele; Pinzon, Eloísa Della Senta; Albrecht, Gustavo Eduardo; Deggerone, Yuri dos Santos; Trentin, Thomas dos Santos; Chiomento, José Luís Trevizan (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate whether the use of on‑farm inoculants based on arbuscular mycorrhizal fungi (AMF) interferes with the agronomic performance of wheat cultivars. The following treatments were applied to cultivars TBIO Calibre and TBIO Sossego: eight on-farm inoculants, i.e., Acaulospora morrowiae, Cetraspora pellucida, Claroideoglomus etunicatum, Glomus intraradices, Rhizophagus clarus, Scutellospora heterogama, and two mycorrhizal communities from native forest (NF) obtained in the Bom Princípio (BP) and in the Flores da Cunha (FC) Brazilian municipalities; and no inoculant (control). A randomized complete block experimental design was used. Mycorrhizal colonization, root morphology, and thousand grain weight were evaluated. The association between 'TBIO Sossego' and S. heterogama provided the greatest root volume, while that between 'TBIO Calibre' and C. etunicatum and between 'TBIO Sossego' and the BP NF community resulted in the best thousand-grain weight. The use of AMF, especially C. etunicatum and S. heterogama, enhances the development of the root system of wheat. 'TBIO Calibre' showed the greatest total length and quantity of very fine roots, while 'TBIO Sossego' developed a root system with the greatest surface area and quantity of thick roots. The use of on-farm inoculants affects the agronomic performance of wheat cultivars.